Comparison of histopathological findings of patients presenting with acute appendicitis in COVID-19 infected and non-COVID-19 infected patients. - Shaikh, M. Faizan; Sajjad, Subhan Ahmed; Ramzan, Owais; Nasir, Shua; Lal Shehbaz; Shaikh, Hafsa Tahir; Hashmi, S. Muhammad Irtiza (International Journal of Endorsing Health Science Research, 2022)
Background: COVID-19 disease has been associated with multiple organs and causes various symptoms depending on the organ involved. Histological findings in the lungs, such as microthrombi, perivascular lymphocytic infiltrate, and necrosis/infarction, can also be seen in the histopathology of the appendix of COVID-19 +ve patients. Methodology: This cross-sectional study was conducted in Dr. Ziauddin Hospital, a tertiary care center in Karachi, Pakistan. In this research article, the histopathology reports of the appendix of COVID-19 +ve patients presenting with acute appendicitis, either antigen or PCR positive, are compared with those of non-COVID patients who presented with acute appendicitis. The data was analyzed using SPSS 20.0, and Pearson’s Chi-Square and Cramer's V tests were performed for analysis. Results: Comparing the histopathology reports of COVID-19 +ve and non-COVID patients presenting with acute appendicitis, an appendix of COVID-19 +ve patients shows microthrombi; perivascular lymphocytic infiltrates, and necrosis/infarction. Conclusion: Patients who are COVID-19 +ve presenting with acute appendicitis should be treated surgically as soon as possible to reduce the risk of acute presentation, ultimately leading to perforation, and not wait for the patient to recover from COVID infection first.